Influence of B4C coating on graphitization for diamond/WC-Fe-Ni composite. (April 2020) - Sun, Youhong; Wu, Jinhao; He, Linkai; Liu, Baochang; Zhang, Chi; Meng, Qingnan; Zhang, Xuliang
Abstract: Diamond/WC-Fe-Ni composite is a potential composition for impregnated diamond drill bits. It is necessary to avoid the graphitization of the diamond from Fe and Ni under the powder metallurgy process. Boron carbide (B4 C) was coated on diamond, and diamond/WC-Fe-Ni composites were consolidated by hot pressing at different temperatures. The influences of sintering temperature and interfacial structure on bending strength and wear behavior were investigated. The bending strength for diamond/WC-Fe-Ni composite was dependent on matrix densification and interfacial graphitization. Un-coated diamond was eroded by Fe-Ni matrix and partially converted to graphite during the sintering process at all sintering temperatures. In opposite, B4 C coating was beneficial to matrix densification at a lower sintering temperature, and delayed the appearance of graphitization to around 1300 °C. Therefore, the diamond/WC-Fe-Ni composites with B4 C coating exhibited larger bending strength and better wear behavior at a relative low sintering temperature. Highlights: B4 C coating is benefit to matrix densification, and delay the diamond graphitization. B4 C coating contributes to enhancement bending strength for diamond/WC-Fe-Ni composite (up to 644 MPa). B4 C coating contributes to improvement in abrasive ratio (up to 2417), increased by 6 times.